Flypaper effect phenomenon on regional spending: Evidence from Lampung province - Suripto, Suripto; Istanti, Istanti; Setyawan, Rai Rake; Aulia, Fina Hajar (Universitas Ahmad Dahlan, 2024)
The existence of constitutional changes due to regional autonomy and changes in financial authority as a result of decentralization are expected to make provinces in Indonesia more flexible in using regional financial budgets. However, the use of regional budgets exceeds central government transfers towards more consumptive regions, which impacts the flypaper effect phenomenon. This study aims to identify the government's fiscal influence on regional spending and the influence of flypaper on the effectiveness of regional spending. The aim of this research is also to analyze the possibility of a flypaper effect on regional spending in districts/cities in Lampung province and to see the influence of own sources revenue (PAD), general allocation funds (DAU), special allocation funds (DAK), profit sharing funds (DBH) on regional spending. Research location in Lampung Province (district/city) for the 2016-2020. The number of samples used was 15 districts/cities. The data source from the Central Statistics Agency (BPS) website is secondary data from the annual Regional Financial Statistics report for Lampung Province. The analytical tool used is panel data regression. The research results show that PAD and DAU are significant to regional spending, while DAK and DBH are not significant to regional expenditures. This indicates that with five years of regional spending, Lampung Province has a flypaper effect phenomenon.